Exploring Sexual Dimorphism in the Intestinal Microbiota of the Yellow Drum (Nibea albiflora, Sciaenidae) - Li, Haidong; Lu, Lei; Chen, Ruiyi; Li, Shanshan; Xu, Dongdong (Frontiers in Microbiology, 2022)
Most of fish species exhibit striking sexual dimorphism, particularly during growth. There are also sexual dimorphisms of internal organs and biological functions, including those of intestinal microbiota, which likely plays a key role in growth. In this study, the growth and intestinal microbiota of the female, male, and all-female Nibea albiflora (yellow drums) were comprehensively analyzed. The caged culture female and all-female yellow drums showed higher growth rates than males. A further analysis of the intestinal microbiota showed a significant difference in diversity between females and males in the summer, whereas there were no significant differences in the diversity and richness between females and males in the winter. In contrast, a significant difference in richness was observed between all-female and male fish, regardless of the season. Although the main composition of the intestinal microbiota showed no significant sex differences, the community structure of the intestinal microbiota of yellow drums did. Furthermore, the correlations between intestinal microbial communities are likely to be influenced by sex. The ecological processes of the intestinal microbial communities of the yellow drums showed clear sexual dimorphism. Further network analysis revealed that, although the main components of the network in the intestinal microbiota of female, male, and all-female fish were similar, the network structures showed significant sex differences. The negative interactions among microbial species were the dominant relationships in the intestinal ecosystem, and Bacteroidetes, Firmicutes, and Proteobacteria were identified as the functional keystone microbes. In addition, the functional pathways in the intestinal microbiota of yellow drums showed no significant sexual or seasonal differences. Based on the findings of this study, we gain a comprehensive understanding of the interactions between sex, growth, and intestinal microbiota in yellow drums.